Industrial–Organizational and Human Factors Graduate Program Admission: Information for Undergraduate Advisors. (January 2015) - Shoenfelt, Elizabeth L.; Stone, Nancy J.; Kottke, Janet L.
Many psychology departments do not have industrial–organizational (IO) or human factors (HF) faculty members. As such, potential IO and HF graduate students may miss career opportunities because faculty advisors are unfamiliar with the disciplines and their graduate programs. To assist advisors, this article highlights the content of IO and HF disciplines, presents tips on how to advise undergraduates for admission to IO and HF graduate programs, provides sources of IO and HF information, suggests employability options in IO and HF, and offers an advising brochure that is available upon request. A wide variety of career options exist in both IO and HF. Advisors assisting students in evaluating potential careers and identifying graduate programs should find this information useful.